(3Gjf GdNdd (B/s - (3GdbQVGhj, jhSas ([(3Ohf ecGf(B] :s (3ecJHI QMGH ddfTQ h GdJhRjY ,s, 1986)
(3gPG GdcJGH Cjf GdNdd jYGdL eTcdI LOjOI LdjdI GdGKQ gh GdOGA GdPj GUGH LSO GdMQcI GdGSdGejI h cJGH HeKGHI GdOhGA GdfGLM h GdYdGL GdGcjO ddMQcI GdZSdGejI aj GbWGQ GdYGde (B. (3jbOe GdeDda GdMd GdGeKd GdPj jQGg aj YOI fbGW h jQi Gf GdMQcI GdGSdGejI YdjgG Gf JdJRe GdUeJ h GdUHQ h GdYed GdOAhH jQi GdeDda Gf JLJeY GdLeGYGJ GdGSdGejI JMJ QGjI hGMOI MJi JMbb GgOGagG h jLH YdjgG JhSjY OGFQJgG h JNUjU GdLRA GdGcHQ ddGLJeGYGJ SjQG Ydi efgL GdGeGe MSf GdHfG (B.(3Gf Gdage GdUMjM ddESdGe h GdYed GdeSJeQ jMbbGf ddMQcI GdGSdGejI JLfH GdeRGdb GdJj bO JYJQVgGs
Keywords: (3GdESdGes; (3GdMQcI GdESdGejIs